Penerapana Metode Problem Solving Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Pada Mata Pelajaran Sosiologi - Fulgensia Halla (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2024)
The purpose of this study was to determine (1) the application of the problem-solving method to improve students' critical thinking in students' sociology learning and (2) the application of the problem-solving method to improve critical thinking skills. The data collection techniques were observation sheets, interviews, tests, and documentation. The data analysis techniques used were qualitative and quantitative data analysis. The results of the classroom action research from the pre-cycle, cycle I to cycle II showed that there was an increase in student learning outcomes in the sociology subject after the problem-solving method was applied to class XI L students of SMAN 5 Kupang. The conclusion is that the application of the problem-solving method to improve students' critical thinking skills in the sociology subject of class XI SMAN 5 Kupang. This was obtained from the results of the implementation of the action, which showed an increase in student learning outcomes in the sociology subject after the problem-solving method was applied. There was an increase in the presentation of learning outcomes totaling from the pre-cycle total score of 1,195 with an average score of 5.85%, Cycle I total score of 1,430 with an average of 6.65%, while cycle II total score of 1,805 with an average of 8.22%. This study shows that the researcher's success criteria have been achieved, namely 80% above the KKM 72.